Inflation Targeting: Evidence for Latin America (1999-2015) - Barros-Campello, Esther; Pateiro-Rodríguez, Carlos; Salcines-Cristal, J. Venancio; Pateiro-López, Carlos (Estudios de Economía, 2017)
In this paper, we discuss the management of monetary policy of the Latin American central banks that have fully established inflation targeting. An optimal monetary rule is estimated for these economies using the Generalized Method of Moments. This analysis allows us to conclude that these central banks have taken into account the economic growth, in addition to price stability. However, only Chile has taken into account the evolution of the exchange rate. Furthermore, Chile, Brazil and Peru have followed an asymmetric behavior, while Colombia and Mexico have adopted a linear monetary policy rule.